2018
DOI: 10.1136/lupus-2018-000285
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation 101: what is important to know about DNA methylation and its role in SLE risk and disease heterogeneity

Abstract: SLE is a complex autoimmune disease that results from the interplay of genetics, epigenetics and environmental exposures. DNA methylation is an epigenetic mechanism that regulates gene expression and tissue differentiation. Among all the epigenetic modifications, DNA methylation perturbations have been the most widely studied in SLE. It mediates processes relevant to SLE, including lymphocyte development, X-chromosome inactivation and the suppression of endogenous retroviruses. The establishment of most DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 175 publications
3
54
0
Order By: Relevance
“…The HLA-DR2 and HLA-DR3 alleles have also been associated with susceptibility and autoantibody production in lupus 12–15 . Overall, hypomethylation of interferon-responsive genes has been associated with higher disease activity and renal disease, as well as production of autoantibodies 1618 . For example, differentially methylated CpGs in TNK2, DUSP5, MAN1C1, PLEKHA1, IRF7, HIF3A, IFI44, and PRR4 have been associated with lupus nephritis 1820 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HLA-DR2 and HLA-DR3 alleles have also been associated with susceptibility and autoantibody production in lupus 12–15 . Overall, hypomethylation of interferon-responsive genes has been associated with higher disease activity and renal disease, as well as production of autoantibodies 1618 . For example, differentially methylated CpGs in TNK2, DUSP5, MAN1C1, PLEKHA1, IRF7, HIF3A, IFI44, and PRR4 have been associated with lupus nephritis 1820 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, hypomethylation of interferon-responsive genes has been associated with higher disease activity and renal disease, as well as production of autoantibodies 1618 . For example, differentially methylated CpGs in TNK2, DUSP5, MAN1C1, PLEKHA1, IRF7, HIF3A, IFI44, and PRR4 have been associated with lupus nephritis 1820 . Differentially methylated CpGs in IFIT1, IFI44L, MX1, RSAD2, OAS1, EIF2AK2 , PARP9/DTX3L , and RABGAP1L have been associated with production of autoantibodies 16,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of IFNs on DNA methylation are not well understood, several studies have reported altered DNA-methylation patterns, including hypomethylation of ISGs in SLE blood cells, which may augment gene expression and thus an IFN signature (reviewed in ref. 70 ). These reports support further investigation of epigenomic signatures and the relationships among IFN signaling, chromatin changes and DNA methylation in autoimmune disease cells.…”
Section: Consequences Of Epigenomic Remodeling By Ifnsmentioning
confidence: 99%
“…Epigenetic changes are prominent in cells and tissues from patients with SLE and a recent, comprehensive review summarises DNA methylation studies in SLE 75. Patients with SLE have decreased methylation levels in a large number of CpG sites and the most strongly hypomethylated genes are IFN regulated 76.…”
Section: Introductionmentioning
confidence: 99%